2014
DOI: 10.1038/ncomms4685
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected interplay of bonding height and energy level alignment at heteromolecular hybrid interfaces

Abstract: Although geometric and electronic properties of any physical or chemical system are always mutually coupled by the rules of quantum mechanics, counterintuitive coincidences between the two are sometimes observed. The coadsorption of the organic molecules 3,4,9,10-perylene tetracarboxylic dianhydride and copper-II-phthalocyanine on Ag(111) represents such a case, since geometric and electronic structures appear to be decoupled: one molecule moves away from the substrate while its electronic structure indicates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
156
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 84 publications
(173 citation statements)
references
References 55 publications
16
156
1
Order By: Relevance
“…(111) compared to the data from UPS measurements. 139 The OT-RSH PDOS shows the important feature of the LUMO pinning at E F , and on top of that corrects the PBE HOMO resonance energy, placing it at 1.6 eV below E F and achieving better agreement with the experiment. OT-RSH and PBE results for the work function change are both very small and close to zero, comparable to experimental results.…”
Section: Ptcda On Ag(111)mentioning
confidence: 71%
“…(111) compared to the data from UPS measurements. 139 The OT-RSH PDOS shows the important feature of the LUMO pinning at E F , and on top of that corrects the PBE HOMO resonance energy, placing it at 1.6 eV below E F and achieving better agreement with the experiment. OT-RSH and PBE results for the work function change are both very small and close to zero, comparable to experimental results.…”
Section: Ptcda On Ag(111)mentioning
confidence: 71%
“…This energetically stabilizes the adsorbate system, which in this case manifests itself in an increased binding energy of the PTCDA LUMO. According to the conjunction of electronic and geometric structure of organic adsorbates (that is, stronger binding goes along with shorter binding distance [6,22]) this is correlated to the observed decrease in the PTCDA adsorption height. In the following two paragraphs we explain the formation of the additional screening mechanism introduced by the CuPc layer in more detail.…”
Section: Discussionmentioning
confidence: 90%
“…In many investigations it was found that the geometric structure and the electronic level alignment at these metal-organic interfaces are determined by the interactions between the molecules themselves, as well as between the molecules and the metal surface. In particular, the charge transfer from the metal substrate into the lowest unoccupied molecular orbital (LUMO), which is the signature of the chemical interaction between the molecule and the surface, is always reflected by the adsorption height of the molecule on the surface [5,6,[21][22][23]. The latter can therefore be seen as a geometric fingerprint of the bonding strength.…”
Section: Introductionmentioning
confidence: 99%
“…Several groups have started to investigate such systems, and, for obvious reasons, prototypical molecules, the homomolecular adsorption of which is well understood, were combined to heteromolecular adsorbate systems in first instance [26][27][28][29][30][31][32][33][34][35][36][37][38][39]. Our group has concentrated on the molecules named above, PTCDA, NTCDA and MePcs, and investigated both laterally mixed structures (i.e., two molecules in different stoichiometries combined in one layer) [40][41][42] and heteromolecular stacks of layers whereby each individual layer contains only one species [43][44][45][46].…”
Section: Introductionmentioning
confidence: 98%
“…In this review paper we present an overview over the activities of our group regarding laterally mixed structures [40][41][42]. We combine investigations of geometric and electronic structure and focus on the interplay of the bonding heights of the molecules and the energy level alignment at the heteromolecular interface.…”
Section: Introductionmentioning
confidence: 99%